Clinical and physiological advances in sedentary behavior research - Heinonen, Ilkka (Frontiers in Physiology, 2024)
Sedentary behavior, defined as sitting with low energy expenditure, has emerged as a modifiable risk factor that affects our physiology and health. Evidence for the detrimental effects of sedentary behavior/physical inactivity on health, however, stems largely from epidemiological studies, which cannot address causalities. Acute and short-term sedentary behavior reduction interventions have been performed; however, in these studies, sitting has often been replaced by formal physical activity options, such as exercise, and long-term studies in subjects with cardiometabolic risk factors are still relatively few. We have recently conducted a long-term randomized controlled trial (RCT) to reduce daily sitting, without formal exercise, in metabolic syndrome patients, and this mini-review presents these studies with physiological aspects. The findings indicate that sedentary behavior reduction can prevent the increase in levels of many cardiometabolic risk factors after 3 months, but more intense physical activity rather than only reducing daily sitting time may be needed to further reduce the risk factor levels. At 6-month time point reduced sitting reduced fasting insulin, while successfully reducing sitting and body fat had beneficial effects also on whole-body insulin sensitivity, but other effects were relatively minor. Reduced sitting did not improve maximal aerobic fitness after 6 months, but an increase in daily steps was positively associated with an increase in fitness. However, the more the participants replaced sitting with standing, the more their maximal aerobic fitness was reduced. Overall, although the analysis of the collected data is still ongoing, our RCT findings suggest that the physiological and health effects of reduced sitting are relatively minor and that physical activities such as taking more daily walking steps are needed, which would be more beneficial and time-efficient for improving human health.